ANALISIS EFEKTIVITAS SISTEM EMR DALAM MENUNJANG MANAJEMEN PENGAMBILAN KEPUTUSAN IGD DI RUMAH SAKIT SANTOSA BANDUNG CENTRAL - Tiara Sandi; Shinta Elvira (Jurnal Infokes, 2026)
Based on the Minister of Health Regulation Number 24 of 2022 concerning Medical Records, all health care facilities are required to implement an electronic medical record system. This EMR system must have compatibility capabilities and with other systems. This study aims to analyze the effectiveness of the EMR system in supporting decision-making management in the Emergency Department (IGD) of Santosa Hospital, Central Bandung. This study uses a qualitative method. The study was conducted at Santosa Hospital, Central Bandung from June to August 2025. The subjects of this study were medical records and one reporting officer selected using Based on the Minister of Health Regulation Number 24 of 2022 concerning Medical Records, all health care facilities are required to implement an electronic medical record system. This EMR system must have compatibility capabilities and with other systems. This study aims to analyze the effectiveness of the EMR system in supporting decision-making management in the Emergency Department (IGD) of Santosa Hospital Bandung Central. This study uses a qualitative method. The study was conducted at Santosa Hospital Bandung Central from June to August 2025. The subjects of this study used a purposive sampling technique. Data collection was conducted through documentation of the patient triage process, the number of triaged patients, and patient triage waiting times recorded in the EMR system. In addition, data was obtained from reporting officers at Santosa Hospital Bandung Central, regarding the 10 most common diseases in the Emergency Department (ER), sourced from routine hospital reports through the EMR system. The results of the study indicate that the implementation of EMR improves the efficiency of patient management time, data accuracy, and service quality in the ER. Based on triage data for the period June-August 2025, the standard patient response time by category (red ≤ 5 minutes, yellow ≤ 10 minutes, green ≤ 30 minutes) was successfully met. In addition, EMR minimizes file duplication, accelerates data access, and supports fast and accurate clinical decision-making. In terms of human resources, healthcare workers have been able to adapt to this system, although it is still in the development stage. Organizational supporting factors and technological aspects also determine the success of the implementation. EMR implementation has proven effective in supporting decision-making in the ER, although periodic evaluation and maintenance of the system is still needed to further optimize its benefits.